Not all permafrost microbiomes are created equal: Influence of permafrost thaw on the soil microbiome in a laboratory incubation study. (April 2022) - Barbato, R.A.; Jones, R.M.; Douglas, T.A.; Doherty, S.J.; Messan, K.; Foley, K.L.; Perkins, E.J.; Thurston, A.K.; Garcia-Reyero, N.
Abstract: Permafrost is thawing at unprecedented rates, significantly altering landscapes and ecosystem trajectories by changing subsurface conditions, vegetation characteristics, and soil properties. Dormant microbes become active as temperatures rise and permafrost soils warm and thaw. To determine the effects of sample location and warming on the permafrost microbiome, we collected permafrost from five distinct locations within the Cold Regions Research and Engineering Laboratory's Permafrost Tunnel (PT) near Fairbanks, Alaska and warmed them in a laboratory incubation study. Heterotrophic respiration was continuously monitored and metagenomes were analyzed at select incubation temperatures. Under frozen conditions, microbial respiration rates from different PT locations were similar, ranging from 2 to 12 mg C–CO2 kg −1 d −1 . During thaw, respiration increased in samples from three PT locations, but remained stable for two locations. Analysis of the shotgun metagenomes showed how the microbial communities and their potential function changed as a function of location and incubation temperature. This indicates a differential response of permafrost microbes based on their origin. These findings have important implications for developing accurate forecasts of microbial community assemblages during thaw in that location should be considered as a strong influencing factor. Graphical abstract: Image 1 Highlights: Dormant microbes activate as temperatures rise and permafrost soils warm and thaw. Cumulative heterotrophic respiration varied by permafrost location during thaw. Permafrost microorganisms were heterogeneously distributed in both space and time. Thaw impacted potential microbial function. Heterogeneously distributed permafrost microbes enable more accurate predictions.